Analysis of the factors affecting taxpayer compliance - Meidawati, Neni; Nanindyas Dewi Waluristyaningtyas (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2023)
The purpose of this research is to analyze the factors that influence the compliance of individual taxpayers in Sleman Regency encompassing tax sanctions, taxpayer awareness, service quality, application of e-filing system, and tax amnesty. Of the population of individual taxpayers who lived in Sleman Regency, 80 respondents were selected as a sample. The method used in this research is multiple linear regression analysis. The results of the study prove that tax sanctions, service quality, taxpayer awareness, and application of e-filing system have positive and significant effects, while tax amnesty has no effect on the compliance of the individual taxpayers in Sleman Regency. Thus, the government must continue to disseminate the importance of tax amnesty for the benefit of both taxpayers and government, considering that tax provides as a source of state revenue. However, it is still indicated that tax amnesty has not yet showed an effect to the taxpayers.